Haliphthoros milfordensis isolated from eggs and larvae of mud crab (Scylla tranquebarica) in Sabah, Malaysia - Lee, Yih Nin; Hatai, K.; Kurata, O. (2017)
Fungal infection occurred during mud crab spawning in a hatchery and caused almost 100% mortality in mud crab larvae after 5 days post-hatching. A fungus was isolated from eggs and larvae using PYGS agar and named IPMB 1603. During morphological identification, the strain IPMB 1603 was observed to produce a fragment inside the hyphae and the zoospores swam away from the tips of the discharge tube on several occasions, this closely resembling the genus Haliphthoros. Following comparisons made on the nucleotide sequence of the ITS1 region, the strain IPMB 1603 was identified belonging to a cluster of Haliphthoros milfordensis sharing 97-100% similarity. In this study, the strain IPMB 1603 was found to be an euryhaline fungus as the strain was able to grow on PYG agar containing NaCl. Strain IPMB 1603 only grew at certain salinity ranges, in which on PYGS agar contained sea water higher than 10 ppt. The optimum temperature range for fungal growth of strain IPMB 1603 was 30-35cC. Different growth rates were demonstrated at pH ranging from 4 to 9, but optimum growth was observed at pH 6 to 8. This is the first record of Haliphthoros milfordensis infection in Malaysia.